Role of culture in pursuit of nation’s progress: the case of ‘Bushido’ - Fathil, Fauziah (KIRKHS, IIUM, 2022)
Bushido or samurai code of ethics, though dated back to feudal Japan, continues to survive until present day in the daily conduct of Japanese for not only it contributed to the solidarity of the people as one nation, but as the impetus for the country’s advancement and progress.